Formaldehyde in Seafood: A review - Laly, S J; Priya, E. R.; Panda, S. K.; Zynudheen, A. A. (Fishery Technology, 2018)
Seafood is a nutrient rich commodity accepted allover the world. Illegal addition of formalin (37%formaldehyde) to seafood for extending shelf lifeaffects the health of consumers as it is identified asa potential carcinogen by International Agency forResearch on Cancer (IARC). The occurrence ofnaturally varying levels of formaldehyde present indifferent food materials including seafood due topost-mortem enzymatic reaction makes the monitoringof illegally added formalin difficult. Understandingthe natural levels of free formaldehydealong with proper regulation and monitoring of thisharmful chemical is essential for safeguardinghealth of seafood consumers.